Association between digital literacy and mental health among older adults in Heilongjiang province: a cross-sectional study of the mediating role of digital health literacy - Zeyu YAN; Zixuan LIU; Yue MA; Ziyu WANG; Kai ZHENG; Qiaoqiao REN; Yanhua HAO (Zhongguo gonggong weisheng, 2025)
ObjectiveTo investigate the digital literacy, digital health literacy, and mental health status of the elderly in Heilongjiang province, and to explore the relationships among these three factors, thereby providing a reference for improving the mental health of this population. MethodsA face-to-face interview was conducted among 800 residents aged ≥ 60 years, recruited using stratified cluster sampling in two cities of Heilongjiang province in August 2024. A self-developed questionnaire on demographics, digital literacy, and digital health literacy, along with the simplified version of the Center for Epidemiologic Studies Depression Scale (CES-D), the six-item UCLA Loneliness Scale (ULS-6), and the Satisfaction with Life Scale (SWLS), was used in the survey. AMOS 28 software was used to analyze the relationships among the three, and the bootstrap method was used to test the mediating effect. ResultsValid information was collected from all participants. Participants′ total scores and scoring indices were as follows: digital literacy (15.30 ± 14.23, 31.9%), digital health literacy (30.60 ± 16.56, 40.8%), and mental health (55.59 ± 11.96, 84.2%). Digital literacy positively predicted digital health literacy (standardized beta = 1.021, 95% confidence interval [95%CI]: 1.006 - 1.034), and digital health literacy positively predicted mental health (standardized beta = 0.601, 95%CI: 0.014 - 2.526). The mediating effect of digital health literacy on the relationship between digital literacy and mental health was significant (standardized beta = 0.613, 95%CI: 0.013 - 2.522). ConclusionsThe digital literacy and digital health literacy of the elderly in Heilongjiang province are relatively low. Digital health literacy plays a mediating role in the relationship between digital literacy and mental health. Improving the digital literacy of the elderly is of great importance in promoting their digital health behaviors and mental health.